2021
DOI: 10.4049/jimmunol.2000887
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 Modulates Processing of Asthma-Related Primary MicroRNAs (Pri-miRNAs) into Mature miRNAs in Lung Epithelial Cells

Abstract: Protein arginine methyltransferase-1 (PRMT1) is an important epigenetic regulator of cell function and contributes to inflammation and remodeling in asthma in a cell type-specific manner. Disease-specific expression patterns of microRNAs (miRNA) are associated with chronic inflammatory lung diseases, including asthma. The de novo synthesis of miRNA depends on the transcription of primary miRNA (pri-miRNA) transcript. This study assessed the role of PRMT1 on pri-miRNA to mature miRNA process in lung epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…Studies have found that PRMT1 is involved in the development and diseases of the nervous system and plays an important role in neurodegenerative diseases [30]. PRMT1 also promotes asthma by regulating asthma-related pri-let-7i and pri-miR-423 [31]. PRMT1-v2 activated the gluconeogenic program in hepatocytes via interactions with PGC1α, a key transcriptional coactivator regulating gluconeogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that PRMT1 is involved in the development and diseases of the nervous system and plays an important role in neurodegenerative diseases [30]. PRMT1 also promotes asthma by regulating asthma-related pri-let-7i and pri-miR-423 [31]. PRMT1-v2 activated the gluconeogenic program in hepatocytes via interactions with PGC1α, a key transcriptional coactivator regulating gluconeogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“… 85 More recently, it was shown that PRMT1 regulates processing of asthma-related miRNAs in lung epithelial cells. 86 PRMT1 is recruited, in complex with either STAT1 or RUNX1, to promote processing of miRNAs upregulated alongside PRMT1 in patients with asthma in response to transforming growth factor beta 1 (TGF-β1). 86 These findings suggest a role for PRMT1 in acute and chronic asthma in epithelial cells and fibroblasts.…”
Section: Prmts In Immune Diseasesmentioning
confidence: 99%
“… 86 PRMT1 is recruited, in complex with either STAT1 or RUNX1, to promote processing of miRNAs upregulated alongside PRMT1 in patients with asthma in response to transforming growth factor beta 1 (TGF-β1). 86 These findings suggest a role for PRMT1 in acute and chronic asthma in epithelial cells and fibroblasts. Furthermore, these findings have implications for the treatment of acute and chronic asthma as PRMT1 could serve as a specific therapeutic target.…”
Section: Prmts In Immune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Remodeling parameters of human airway fibroblasts were also upregulated via PRMT1 and a signaling pathway involving C/EBP-β, leading to mitochondrial activity [98][99][100]. In airway epithelial cells, the processing of microRNAs might increase the susceptibility to develop asthma [101]. However, the role of the different HSPs and their variants in the context of asthma-associated airway wall remodeling is controversial and has to be further investigated [102].…”
Section: The Epithelium As the Central Regulator Of The Airway Wallmentioning
confidence: 99%